1909 Me. Laws 141, An Act to prohibit the use of Firearms fitted with any device to deaden the sound of explosion, ch. 129, § 1 - (:unkn) unknown (General Publisher, 1909)
It shall be unlawful for any person to sell, offer for sale, use or have in his possession, any gun, pistol or other firearm, fitted or contrived with any device for deadening the sound of explosion. Whoever violates any of the provisions of this act shall forfeit such firearm or firearms and the device or silencer, and shall further be subject to a fine not exceeding one hundred dollars, or to imprisonment not exceeding sixty days, or to both fine and imprisonment. . .
--
Keywords: SUPPRESSORS